The effects of minimum wage hikes on employment and wages in Viet Nam's micro, small, and medium enterprises - Phan Kim Dung (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Very little is known about the extent to which wage and employment offsetting behaviours change by firm size to mitigate the detrimental effects of minimum wage regulation. Do micro establishments react more aggressively to minimum wage shocks compared to small and medium establishments? To answer this question, this paper examines the impact of minimum wage hikes on employment and wages in Viet Nam's micro enterprises, and small and medium enterprises (SMEs), respectively. In particular, I exploit the differences in the rates of increases in minimum wages across minimum wage regions to identify the effects of minimum wage changes. The findings indicate that minimum wage has greater employment effects on SMEs, but alters employment structure of micro firms.
Keywords: J38; 330; minimum wage; employment; wage